Comparing SARS-CoV-2 variants among children and adolescents in Germany: relative risk of COVID-19-related hospitalization, ICU admission and mortality - Jank, Marietta; Oechsle, Anna-Lisa; Armann, Jakob; Behrends, Uta; Berner, Reinhard; Chao, Cho-Ming; Diffloth, Natalie; Doenhardt, Maren; Hansen, Gesine; Hufnagel, Markus; Lander, Fabian; Liese, Johannes G.; et al. (Infection, 2023)
SARS-CoV-2 infections cause COVID-19 and have a wide spectrum of morbidity. Severe disease courses among children are rare. To date, data on the variability of morbidity in relation to variant of concern (VOC) in children has been sparse and inconclusive. We compare the clinical severity of SARS-CoV-2 infection among children and adolescents in Germany during the Wildtype and Alpha combined, Delta and Omicron phases of the COVID-19 pandemic.
Online veröffentlicht: 14. Februar 2023
Gesehen am 02.09.2024